Long-term safety of certolizumab pegol in rheumatoid arthritis, axial spondyloarthritis, psoriatic arthritis, psoriasis and Crohn’s disease: a pooled analysis of 11 317 patients across clinical trials - Tore K Kvien; Xavier Mariette; Jeffrey R Curtis; Vivian P Bykerk; William J Sandborn; Cécile Gaujoux-Viala; Andrew Blauvelt; Kevin Winthrop; Marc de Longueville; Ivo Huybrechts (RMD Open)
Objective To review long-term certolizumab pegol (CZP) safety across all approved indications: rheumatoid arthritis (RA), axial spondyloarthritis (axSpA), psoriatic arthritis (PsA), psoriasis (PSO) and Crohn’s disease (CD).Methods Data were pooled across 49 UCB-sponsored CZP clinical trials (27 RA, one axSpA, one PsA, five PSO, 15 CD) to August 2017. Serious adverse events (SAEs) of interest (infections, malignancies, autoimmunity/hypersensitivity events, major adverse cardiovascular events (MACE), gastrointestinal (GI) perforations, psoriasis events, laboratory abnormalities) and deaths were medically reviewed by an external expert committee, using predefined case rules. Incidence rates (IRs)/100 patient-years (PY) are presented by indication; standardised mortality and malignancy rates were calculated using WHO/GLOBOCAN/SEER databases. Pregnancies with maternal CZP exposure are also reported.Results Of 11 317 CZP-treated patients across indications (21 695 PY CZP exposure; maximum: 7.8 years), infections were the most common SAEs (overall IR: 3.62/100 PY; IRs ranged from 1.50/100 PY(PSO) to 5.97/100 PY(CD)). The IR for malignancies was 0.82/100 PY, including lymphoma (0.06/100 PY). MACE and GI perforation IRs in CZP-treated patients were 0.47/100 PY and 0.08/100 PY and were highest in RA and CD, respectively. Patients with PSO had the lowest SAE rates. The incidence of deaths and malignancies aligned with expected general population data.Conclusion This extensive overview of the CZP safety profile in clinical trials, across all indications, provides large-scale confirmation of previous reports. No new safety signals or relevant non-disease-related laboratory abnormalities were identified. The study demonstrated some indication-specific differences in certain SAE rates that may be attributable to the underlying inflammatory disease.